Monocytosis and Multiple Myeloma: treatment-related acute leukaemia? - Cristina Veronica Trinidad Esparza; Maria J. Lizardo-Thiebaud; María Graciela Leal-Gutierrez; Beatriz Sánchez-Hernandez; Daniel Montante Montes de Oca (Surgical and Experimental Pathology, 2022)
Abstract Background Therapy-related acute monocytic leukemias in patients with plasma cell dyscrasias are infrequent. Case presentation We here present a case of a 60 year old female who developed an acute monocytic leukemia two years after the diagnosis of multiple myeloma. She was treated with an alkylating agent and bortezomib before undergoing a hematopoietic stem cell transplantation. She suffered of multiple severe infections until her immune system was adequately reconstituted. A year afterwards, she presented signs of deterioration unrelated to the MM, with pancytopenia. The bone marrow aspirate failed to show a prominent blast population. The diagnosis of AML was confirmed after a bone marrow biopsy. Discussion The development of acute leukaemia after treatment for multiple myeloma is a well characterized phenomenon. Most frequently, patients develop a myelomonocytic leukemia. Similarly, synchronous acute myeloid leukemias are myelomonocytic or myeloblastic. Rarely synchronous AMLs are monocytic. The development of such suggests a dysfunctional bone marrow microenvironment.